Nephroprotective and anticoagulant therapy in patients with atrial fibrillation and chronic kidney disease: real-world data - A. I. Listratov; I. I. Ivanov; N. K. Ziskina; V. V. Efimenko; A. V. Zhavoronkova; E. S. Milyakova; A. A. Kudrjavtseva; D. A. Napalkov; A. A. Sokolova (Рациональная фармакотерапия в кардиологии)
Aim. To assess the compliance of nephroprotective and anticoagulant therapy in patients with atrial fibrillation (AF) and chronic kidney disease (CKD) with modern clinical guidelines.Material and methods. The study included patients with CKD in combination with AF and in sinus rhythm. Clinical characteristics were retrospectively assessed, as were the use of renin-angiotensin system inhibitors (RASi), statins, sodium-glucose transporter type 2 inhibitors (SGLT-2i) and oral anticoagulants (OAC).Results. A total of 464 patients (aged 66-80 years) were divided retrospectively in two subgroups — with and without AF. AF was detected in 210 (45.3%) patients. Patients from the subgroup with AF were significantly older (75 vs 72 years, p=0.001), more often had type 2 diabetes mellitus (T2DM) (28.6% vs 20.5%, p=0.042), coronary artery disease (CAD) (40.5% vs 30.7%, p=0.028) and chronic heart failure (CHF). (57.6% vs 22.8%, p<0.001). Mean estimated glomerular filtration rate (eGFR) according to Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation was lower (46 vs 51 ml/min/1.73 m2, p<0.001) in patients with AF compared with the group without AF. ACE inhibitors (ACEi) were prescribed in 127 cases (27.4%), angiotensin II receptor blockers (ARBs) — in 227 (49%), angiotensin receptor neprilysin inhibitor (ARNI) — 33 (7.1%), statins — 362 (78%), SGLT2i — 63 (13.6%), direct oral anticoagulants (DOACs) — 203 (43.8%) and warfarin — in 10 cases (2.2%). In those patients in whom SGLT2i was prescribed, eGFR according to the CKD-EPI equation was significantly lower (47 vs 49 ml/min/1.73 m2, p=0.043). In patients with T2DM, SGLT-2i-2 was prescribed in 33.9% of cases, in patients with chronic heart failure with reduced ejection fraction (CHFrEF) — in 68.4% of cases. In 196 patients with AF, DOACs were prescribed, in 10 cases — warfarin.Conclusion. Most patients with CKD receive nephroprotective therapy with RASi and statins according to current KDIGO guidelines. A significant proportion of patients with CHFrEF receive SGLT-2i, but only a third of patients with T2DM and CKD received SGLT-2i therapy.